HUBUNGAN ANTARA KEMANDIRIAN BELAJAR DENGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Suryana, Alya; Rosdianto, Haris Rosdianto; Utama, Erdi Guna (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2024)
Abstract; This study aims to determine the relationship between learning independence and the mathematical problem solving ability of elementary school students. The method used is correlation research. The population in this study was all grade IV students of SDIT Nurul Islam which amounted to 62 students. The sampling technique uses saturated sampling, where all members of the population are sampled. The data collection techniques in this study used non-test techniques, questionnaires, learning independence, and test techniques on mathematical problem-solving abilities. The data analysis technique used is the Pearson Product Moment Correlation. The results showed that: 1) the level of learning independence was moderate with an average score of 83, 2) the level of mathematical problem solving ability was moderate with an average score of 64, 3) there was a relationship between learning independence and students' mathematical problem solving ability on fractional material with a correlation coefficient value () of 0.45 and a coefficient of determination of 20.25 %. So, it can be concluded that there is a strong enough relationship between learning independence and mathematical problem solving skills.